Standardized Volume Dosing Protocol of 23.4% Hypertonic Saline for Pediatric Critical Care: Initial Experience. Issue 9 (September 2020) - Cummings, Brian M.; Fernandes, Neil D.; Parker, Lois F.; Murphy, Sarah A.; Yager, Phoebe H.
Background: Standardized volume dosing of 23.4% hypertonic saline (HTS) exists for adults, but the concentration, dosing and administration of HTS in pediatrics is variable. With emerging pediatric experience of 23.4% HTS, a standard volume dose approach may be helpful.Objective: To describe initial experience with a standardized 23.4% HTS weight-based volume dosing protocol of 10, 20, or 30 mL in the pediatric intensive care unit.Methods: Standard volume doses of 23.4% HTS were developed from weight dosing equivalents of 3% HTS. Pre and post sodium and intracranial pressure (ICP) measurements were compared with paired t-test or Wilcoxon rank-sum test. The site of administration and complications were noted.Results: A total of 16 pediatric patients received 37 doses of 23.4% HTS, with the smallest patient weighing 11 kg. For protocol compliance, 17 doses (46%) followed recommended dosing, 19 were less volume than recommended (51%), and 1 dose (3%) was more than recommended. Mean increase in sodium was 3.5 mEq/L (95% CI = 2-5 mEq/L); P < 0.0001. The median decrease in ICP was 10.5 mm Hg (interquartile range [IQR] 8.3-19.5) for a 37% (IQR 25%-64%) reduction. Most doses were administered through central venous access, although peripheral intravenous administrations occurred in 4 patients without complication.Conclusion and Relevance: Three standard-volume dose options of 23.4% HTS based on weight increases sodium and reduces ICP in pediatric patients. Standard-volume doses may simplify weight-based dosing, storage and administration for pediatric emergencies, although the optimum dose, and safety of 23.4% HTS in children remains unknown.